Adaptation Of Religious Patterns Of International Students In A Pesantren-Based Islamic Higher Education Environment At Universitas Islam Darul Ulum, Lamongan - Aisyah Aini Rokhmah; Sauqi Futaqi; Ali Musyafa’ (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the adaptation of religious patterns among international students within an Islamic education environment based on the pesantren system at Universitas Islam Darul Ulum (UNISDA), Lamongan. The pesantren environment is characterized by a structured religious life rooted in Indonesian Islamic traditions, which requires international students to adjust their religious understanding, practices, and attitudes. This research employs a qualitative approach with a descriptive-exploratory design. The research subjects consist of eight international students from Southern Thailand, Malaysia, the Philippines, and Timor-Leste. Data were collected through in-depth interviews, non-participant observation, and documentation, and were analyzed through the stages of data reduction, data display, and continuous conclusion drawing. The findings indicate that the adaptation of religious patterns among international students occurs gradually and dynamically. Differences in Islamic traditions, language, and religious culture, particularly the dominance of Nahdlatul Ulama (NU) religious practices, constitute initial challenges in the adaptation process. However, social support from peers, lecturers, and the campus environment plays a significant role in assisting students to manage these differences in a moderate and reflective manner.